STRENGTHENING DIPLOMATIC MULTILATERALISM THROUGH ECONOMIC PARTNERSHIP OF BRICS COUNTRIES - Kraktus, Ema (Serbian political thought, 2024)
The BRICS partnership is a multilateral initiative that brings together Brazil, Russia, India, China, South Africa, Egypt, Ethiopia, Iran, the United Arab Emirates, and several other countries with observer status. This alliance emerged as a response to the dominance of Western economies and aimed to create a multipolar world order through primarily economic and, subsequently, political cooperation and the development of alternative financial institutions. Since its inception, BRICS has gained economic power, achieved geopolitical influence, and highlighted the importance of developing “third world countries” and their liberation from the influence of Western colonialist policies. This paper specifically addresses the economic development of BRICS countries and the strategic strengthening of diplomatic multilateralism through economics, viewing BRICS integration processes from a less exploited angle in contemporary Serbian science. The author focuses on the initial members of this organization: Brazil, Russia, India, China, and South Africa.
Keywords: BRICS; economic development; diplomacy; multilateralism; multipolar world order